Stereotype of Poor Peasants of Dnieper Ukraine in the Second Half of the 19th and Early 20th Centuries: Between Ideas and Reality - Voloshenko, Viktoriia (Studia Historiae Oeconomicae, 2025)
In the article, the author analyzes the transformations of the stereotype of peasant poverty of Dnieper Ukraine[1] in the second half of the 19th and early 20th centuries; examines the spaces of its formation and the image of the reality of peasant poverty enshrined in contemporary Ukrainian historiography; proves that this stereotype conceals both a real phenomenon and a cultural construct generated by it. The emergence of the stereotype was a social reaction to the economic conditions of peasants, and was entrenched in publicism and fiction. Its replication contributed to the formation of the corresponding peasant auto-stereotype. The emotionally colored rhetoric of describing “miserable” peasants was used to draw attention to the severity of this problem or other social, political, or economic issues; to mobilize the population around the government or opposition forces within groups; to implement civic initiatives; and to take into account the specifics of the worldview of the imagery of the writers who addressed this topic. With the Bolsheviks’ rise to power, this stereotype was politically instrumentalized to the utmost. The deconstruction of the Soviet topos of poverty perception in contemporary Ukrainian historiography is accompanied by an update of the conceptual apparatus. Despite the absence of a special study on this topic, the works of Ukrainian historians highlight 1) the structural factors of peasant poverty; 2) the local and family dimensions of peasant impoverishment; and 3) scenarios for getting out of poverty. Ukrainian scholars show that for peasants, poverty could be not only a problem but also an incentive for radical change. On the other hand, peasant ways of preventing poverty may have been inaccessible to those whose condition could already be characterized as “poverty”. Moreover, poverty preventive measures could act as catalysts for deepening poverty. Ukrainian scholars also point to the conditional nature of peasant poverty and the difficulty in determining criteria for its assessment.